Kuwait : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Kuwait. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that decline in oil prices has adversely affected Kuwait's fiscal and current account balances and slowed growth in 2014-15. Real non-oil GDP growth is projected to slow in 2015 and 2016, and pick up to 4 percent in the medium term, supported by government investment in infrastructure and private investment. The fiscal and external positions are projected to deteriorate further in 2015 and 2016, and improve somewhat over the medium term as oil prices and production recover partially.